Atlas of Chad's rangelands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
One of the goals of CTA is to bring together dispersed information and knowledge in order to make it available to a larger number of users. This is particularly important when dealing with the problems caused by the drought in the Sahel. Hence a...